Indirect Neuromonitoring of the Spinal Cord by Near-Infrared Spectroscopy of the Paraspinous Thoracic and Lumbar Muscles in Aortic Surgery - Luehr, Maximilian; Mohr, Friedrich-Wilhelm; Etz, Christian D. (The Thoracic and Cardiovascular Surgeon, 2016)
Paraplegia remains the most devastating complication of open and endovascular thoracic/thoracoabdominal aortic aneurysm (TAA/A) repair. However, the assessment of currently available neuromonitoring modalities remains challenging and difficult to interpret. Near-infrared spectroscopy (NIRS) has been introduced as a strategy for noninvasive, real-time monitoring of the paraspinous collateral network (CN) to detect potential spinal cord ischemia at our institution. Prior to TAA/A repair, a cerebrospinal fluid catheter is placed and four NIRS optodes are bilaterally positioned on the patient's back to transcutaneously monitor regional muscle oxygenation at the thoracic and lumbar levels. Indirect surveillance of the spinal cord by NIRS seems to be a tempting option with increasing evidence supporting the CN concept.
Keywords: aorta/aortic; spinal cord; aneurysm